Oviposition preference of diamondback moth (Plutella xylostella Linn.) on several species of Brassicaceae Family crops - Muhlison, Wildan; Maslucha, Nurul; Usman, Muhammad; Wagiyana, Wagiyana (Universitas Trunojoyo Madura, 2025)
Diamondback moth (P. xylostella) is a major pest of Brassicaceae crops. This study investigates host plant preferences of P. xylostella and their impact on larval growth across five Brassicaceae species (cabbage, green mustard, cauliflower, kale, and kailan). This experimental using a Completely Randomized Design (CRD) with five replications, we assessed oviposition behavior and larval growth efficiency. The research was conducted at the Agrotechnology Laboratory, Faculty of Agriculture, University of Jember. Our findings reveal that P. xylostella preferred kale (B. oleracea var. sabellica) for oviposition (19 eggs on average), followed by green mustard, cabbage, kailan, and cauliflower. Analysis of the efficiency of conversion of food (ECI and ECD) were highest in larvae fed on kailan leaves, suggesting enhanced larval development (ECI = 0.1966, ECD = 0.2074). These findings suggest that kale could be used as a trap crop in integrated pest management (IPM) strategies to mitigate damage on economically important Brassicaceae crops.